2021
DOI: 10.1007/s10461-020-03138-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Mental Health in the Context of Adolescent Pregnancy and HIV in Sub-Saharan Africa: A Systematic Review Identifying a Critical Evidence Gap

Abstract: Adolescent (10–19 years) mental health remains an overlooked global health issue. Rates of adolescent pregnancy within sub-Saharan Africa are some of the highest in the world and occur at the epicentre of the global HIV epidemic. Both experiencing adolescent pregnancy and living with HIV have been found to be associated with adverse mental health outcomes, when investigated separately. Poor mental health may have implications for both parent and child. The literature regarding mental health within groups exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 89 publications
3
34
0
Order By: Relevance
“…These findings extend literature identifying elevated prevalence of mental health burden among adolescent mothers [23,24] and, highlight increased mental health burden (likely driven by probable depressive symptoms) among adolescents experiencing the dual impact of motherhood and living with HIV. As such, findings address a critical evidence gap as a recent systematic review identified no existing studies reporting the prevalence of common mental disorder among adolescent mothers living with HIV [37]. Adjusted models within analyses also highlight the potential complexity of probable common mental disorder among adolescent mothers within the context of HIV.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…These findings extend literature identifying elevated prevalence of mental health burden among adolescent mothers [23,24] and, highlight increased mental health burden (likely driven by probable depressive symptoms) among adolescents experiencing the dual impact of motherhood and living with HIV. As such, findings address a critical evidence gap as a recent systematic review identified no existing studies reporting the prevalence of common mental disorder among adolescent mothers living with HIV [37]. Adjusted models within analyses also highlight the potential complexity of probable common mental disorder among adolescent mothers within the context of HIV.…”
Section: Discussionmentioning
confidence: 81%
“…The mental health of adolescents living with HIV who have experienced pregnancy/parenthood (both mothers and fathers) in sub-Saharan Africa and, as such, South Africa, is a neglected topic [37]. A recent systematic review exploring common mental disorder within the context of adolescent pregnancy and HIV in sub-Saharan Africa [37] identified only a single prevalence study (undertaken in Kenya) relating to depressive symptomology among a sub-sample of adolescents living with HIV who were currently pregnant (n = 14) [28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations